1984
DOI: 10.1161/01.str.15.2.351
|View full text |Cite
|
Sign up to set email alerts
|

Doppler power frequency spectrum analysis in the diagnosis of carotid artery disease.

Abstract: SUMMARY Power Frequency Spectral Analysis (PFSA) which evaluates the power of the frequency components at a selected interval, was applied in this preliminary study using a 5MHz Doppler continuous wave flow velocity meter and a modified Edwards Spectra view 500 analyzer.PFSA was used to study the common, internal and external carotid arteries of ten young adult control subjects and 31 patients with angiographically documented carotid bifurcation lesions. Two useful indices are described: (1) the frequency band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0
1

Year Published

1985
1985
2002
2002

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 24 publications
2
6
0
1
Order By: Relevance
“…The values of 6 m m or larger recorded in the present study for the diameter of normal internal carotid arteries at the origin, correspond well with the diameters of 6.1 0.72 (SD) mm given by Norrving and Cronquist (1 l), of 7 mm or larger given by Krause et al (16), and with a lumen area of 34 square mm in elderly persons (61-90 years), given by Peterson et al (7).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The values of 6 m m or larger recorded in the present study for the diameter of normal internal carotid arteries at the origin, correspond well with the diameters of 6.1 0.72 (SD) mm given by Norrving and Cronquist (1 l), of 7 mm or larger given by Krause et al (16), and with a lumen area of 34 square mm in elderly persons (61-90 years), given by Peterson et al (7).…”
Section: Discussionsupporting
confidence: 92%
“…Stenoses are frequently only graded as having less than, of more than 50% lumen reduction, or tentatively with a higher precision, with terms such as mild (0-29%), moderate (30-69%) and severe To circumvent this problem, the diameter of the common carotid artery (8), or that of the cranial part of the internal carotid artery on the neck (9-14) have been used as reference. The use of the former tends to overestimate stenosis (8), the latter to underestimate it (15,16). In agreement with this, we found that percentage stenosis, defined as lumen reduction relative to a cranial reference segment, generally is lower than zero in healthy arteries with a carotid bulb.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Recently, Krause and colleagues 24 reported their preliminary experience with continuous-wave Doppler PFSA to detect carotid arterial occlusive disease. Frequency bandwidths at 50% peak power ( f^) were identified as an index of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Krause and colleagues 24 applied power frequency spectrum analysis (PFSA) to carotid continuous-wave ultrasonic Doppler signals. The Doppler signals obtained during an 8-msec interval at peak systole were selected for further processing.…”
mentioning
confidence: 99%